2019
DOI: 10.1021/acs.inorgchem.9b00794
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear Palladacycles of 3-Acetyl-7-methoxy-2H-chromen-2-one Derived Schiff Bases: Efficient Catalysts for Suzuki–Miyaura Coupling in an Aqueous Medium

Abstract: Tetranuclear organopalladium­(II) complexes 1–3 and mononuclear complex 4 have been synthesized by the complexation of 3-acetyl-7-methoxy-2H-chromen-2-one derived Schiff bases with potassium tetrachloropalladate K2[PdCl4]. Structural confirmation for the complexes (1–3) has been achieved by single-crystal X-ray diffraction analysis. The ligands are found to bind with the palladium ion through its azomethine nitrogen, thiolate sulfur, and C4 carbon atom of the coumarin moiety subsequent to C–H activation. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Cationic complexes 23 of the type [Pd(dppe)L]NO3 (dppe = 1,2-bis(diphenylphosphino)ethane), where L is a bidentate thiosemicarbazone ligand derived from a p-substituted benzaldehyde were prepared by Thapa et al, and structurally characterised, confirming the formation of N,S-chelated 5membered rings (Figure 4) [117]. The authors hypothesised that, in view of the previously observed Dharani et al reported a series of palladium complexes 22 derived from 3-acetyl-7-methoxy-2H-chromen-2-one thiosemicarbazones (Figure 3) [115]. Three of the products (22a-c) proved to be tetranuclear complexes in which ligands are bonded via S, N, and C, cyclometallation having taken place by activation of the ortho-C-H bond.…”
Section: Scheme 12 Suzuki Reaction Of Aryl Bromides With Phenylboronmentioning
confidence: 79%
See 1 more Smart Citation
“…Cationic complexes 23 of the type [Pd(dppe)L]NO3 (dppe = 1,2-bis(diphenylphosphino)ethane), where L is a bidentate thiosemicarbazone ligand derived from a p-substituted benzaldehyde were prepared by Thapa et al, and structurally characterised, confirming the formation of N,S-chelated 5membered rings (Figure 4) [117]. The authors hypothesised that, in view of the previously observed Dharani et al reported a series of palladium complexes 22 derived from 3-acetyl-7-methoxy-2H-chromen-2-one thiosemicarbazones (Figure 3) [115]. Three of the products (22a-c) proved to be tetranuclear complexes in which ligands are bonded via S, N, and C, cyclometallation having taken place by activation of the ortho-C-H bond.…”
Section: Scheme 12 Suzuki Reaction Of Aryl Bromides With Phenylboronmentioning
confidence: 79%
“…They were found to have an initial size of 1.5-2.0 nm, but after successive runs they aggregated to larger particles with lower activity. Dharani et al reported a series of palladium complexes 22 derived from 3-acetyl-7-methoxy-2Hchromen-2-one thiosemicarbazones (Figure 3) [115]. Three of the products (22a-c) proved to be tetranuclear complexes in which ligands are bonded via S, N, and C, cyclometallation having taken place by activation of the ortho-C-H bond.…”
Section: Scheme 12 Suzuki Reaction Of Aryl Bromides With Phenylboronmentioning
confidence: 99%
“…[22] Recently, Rathinasabapathi Prabhakaran et al reported tetranuclear palladacycles of 3-acetyl-7-methoxy-2Hchromen-2-one derived Schiff bases, and was found that this complex is very effective for Suzuki-Miyaura coupling in an aqueous medium. [23] Based on the literature evidences, we herein synthesized amino chroman-4-one based amino ligands (L1-L10) and have shown uses in the Suzuki-Miyaura and the Mizoroki-Heck cross-coupling reactions with Pd(II)-salt in aqueous medium under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, they are useful in synthetic organic chemistry, as catalysts in many reactions with formation of C-C and C-N bonds [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%